Teaching Video NeuroImage: Amaurosis Fugax Due to Recurrent Central Retinal Artery Occlusion by Microemboli. (16th August 2022) - Weiss, Viktor; Doležalová, Irena; Mňuk, Tomáš; Labounková, Ivana; Herzig, Roman; Nestrašil, Igor
Abstract : A previously healthy 71-year-old woman with hypercholesterolemia and current tobacco use presented with transient painless vision loss in the left eye without other neurologic abnormalities. The 30-second episodes, followed by a recovery, repeated in 2- to 3-minute intervals. 1 Microemboli passing through central retinal artery (CRA) vasculature (Video 1) originated from a complicated atherosclerotic plaque in the left internal carotid artery (Figure). After receiving intravenous thrombolysis 5 hours after symptom onset, 2 she reported a scotoma in the inferior part of her left eye, which persisted 2 years later. Retinal embolism from carotid artery disease is the most common cause of CRA occlusion.